Respuesta :

Answer:

4 - 12x

Step-by-step explanation:

-6(-2/3 + 2x)

we can distribute by multiplying -6 by whats inside of the parenthesis ( -2/3 and 2x )

-6 * -2/3 = 4

-6 * 2x = -12x

4 - 12x would be the equivalent expression

Given :

  • A expression -6(2/3 +2x).

To Find:

  • The equivalent expression from the options.

Solution :-

Given expression to us is ,

→ -6( -2/3 +2x)

Simplify by multiplying each terms inside the brackets by -6 .

→ -6*-2/3 + 2x*(-6)

Simplify,

→ 4 -12x

Hence option 3 is correct .

I hope this helps .